Agility design and deployment framework: case of forest products industry. (1st January 2014) - Boughzala, Dhiaeddine; Nourelfath, Mustapha; Frayret, Jean-Marc; Léger, François
This paper designs our agility framework applied to the forest products industry. We aim to provide an end-to-end process covering enterprise modelling, turbulences understanding, agility drivers' definition and finally change/actions analysis. The industrial context and the research problem are first explored. A multidimensional agility design and deployment framework is developed considering conceptual, contextual, experimental and decisional dimensions. The first two dimensions give the specification components of the agility as a high-level vision. The experimental dimension serves first to validate interactions within the model, then as a tool to assess risk, opportunities and potential solutions. The decisional dimension is then introduced as a complement to develop the ability to face unexpected changes and especially to analyse orientations. A proof-of-concept called LOGI LUMBER supply chain is used throughout the framework development. Two experimental generations were accomplished based on 15 scenarios run and analysed with our modelling and optimisation software called LogiLab .